2005
DOI: 10.1152/ajprenal.00202.2004
|View full text |Cite
|
Sign up to set email alerts
|

Primary human glomerular endothelial cells produce proteoglycans, and puromycin affects their posttranslational modification

Abstract: This article describes the possible role of the endothelial cell-surface coat, containing proteoglycans (PGs) with connected glycosaminoglycans (GAGs), in maintaining glomerular permselectivity. Primary human glomerular endothelial cells (HGEC) in culture were treated with the nephrosis-inducing agent puromycin aminonucleoside (PAN). Analysis was made by TaqMan real-time PCR, Western blot analysis, and by metabolic labeling with [(35)S]sulfate. The HGECs express several PGs: syndecan, versican, glypican, perle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 51 publications
4
53
0
Order By: Relevance
“…More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 73%
“…Versican is an extracellular matrix proteoglycan with chondroitin sulphate chains that are able to bind hyaluronic acid [44]. We have recently found it to be expressed by human glomerular endothelial cells [10] and versican is most likely a component of the endothelial cell glycocalyx. Furthermore, in previous studies we have shown that digestion of hyaluronic acid and/or chondroitin sulphate in the glomerular endothelial cell glycocalyx increases the fractional clearance for albumin [9,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The differences between our study and previous studies could simply be due to differences in the antibody affinity or to the examination of different stages of renal disease. In addition, the functional role or roles of biglycan are unclear; roles have been proposed in the maintenance of the glomerular charge barrier, 48,49 in the regulation of mesangial cell growth and survival, 50 in the regulation of TGF-␤ activity, 51 in the regulation of inflammation via activation of Toll-like receptors, 52 in the regulation of the assembly of connective tissues, 53 and in the structural composition of fibrosis, 22 among others. Both biglycan and decorin can bind TGF-␤, leading to its sequestration and neutralization of activity.…”
Section: Discussionmentioning
confidence: 99%
“…The second protein identified was LG3, the C-terminal domain of Perlecan, a proteoglycan found in the filtration barrier and expressed in all basement membranes (41,42). Although Perlecan has a proangiogenic role (43), its domain V, C-terminal fragment Endorepellin has potent antiangiogenic properties (44), providing it with a potential role in the development of a relatively avascular scar tissue that partially leads to progressive renal damage.…”
Section: Discussionmentioning
confidence: 99%